2021
DOI: 10.1155/2021/5598824
|View full text |Cite
|
Sign up to set email alerts
|

A Nomogram Prediction of Length of Hospital Stay in Patients with COVID-19 Pneumonia: A Retrospective Cohort Study

Abstract: Assessing the length of hospital stay (LOS) in patients with coronavirus disease 2019 (COVID-19) pneumonia is helpful in optimizing the use efficiency of hospital beds and medical resources and relieving medical resource shortages. This retrospective cohort study of 97 patients was conducted at Beijing You’An Hospital between January 21, 2020, and March 21, 2020. A multivariate Cox proportional hazards regression based on the smallest Akaike information criterion value was used to select demographic and clinic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
13
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(16 citation statements)
references
References 16 publications
(21 reference statements)
3
13
0
Order By: Relevance
“…Laboratory results obtained from the blood of COVID-19 patients can be identified as affecting on the patient's LOS. High levels of alanine aminotransferase (ALT) and aspartate aminotransferase (AST) (>40 U/L) and high myoglobin on laboratory tests were also identified as being able to increase LOS in COVID-19 patients (Li et al, 2021). In addition, the Systemic Inflammation Index (SII) is a count of [neutrophils × platelets]/lymphocytes having a significant effect on the length of hospital stay.…”
Section: Laboratory Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Laboratory results obtained from the blood of COVID-19 patients can be identified as affecting on the patient's LOS. High levels of alanine aminotransferase (ALT) and aspartate aminotransferase (AST) (>40 U/L) and high myoglobin on laboratory tests were also identified as being able to increase LOS in COVID-19 patients (Li et al, 2021). In addition, the Systemic Inflammation Index (SII) is a count of [neutrophils × platelets]/lymphocytes having a significant effect on the length of hospital stay.…”
Section: Laboratory Resultsmentioning
confidence: 99%
“…Research shows that age > 50 can increase the risk of patient severity, so a long time is needed for in-hospital treatment (Li et al, 2021). Patients over 65 years of age have the highest severity and the lowest in children under 18 years of age (Stokes et al, 2020).…”
Section: Agementioning
confidence: 99%
See 1 more Smart Citation
“…Two previous studies were used to predict LOS in SARS-CoV-2 patients. However, in one study, the variables of the model contained “Wuhan travelling history” [ 11 ], and in another the virus was not Omicron variant [ 12 ]. Therefore, it is an urgent need to develop a validated predictive model to predict LOS in Omicron patients, which can optimize the management of patients to alleviate the strain on medical resources.…”
Section: Introductionmentioning
confidence: 99%
“…Studies have indicated that the mean LOS of patients hospitalized for COVID-19 ranges from 5 to 17 days [ 11 , 12 , 13 , 14 , 15 , 16 , 17 , 18 ]. A patient’s LOS is influenced by various clinical and personal factors, and some clinical tools have been developed to predict patients’ LOSs [ 19 , 20 ]. Patients with multiple comorbidities [ 11 , 17 , 18 , 21 , 22 ] and older age [ 18 , 23 , 24 ] are more vulnerable and associated with prolonged LOS for COVID-19.…”
Section: Introductionmentioning
confidence: 99%